2017
DOI: 10.1158/0008-5472.can-17-0484
|View full text |Cite
|
Sign up to set email alerts
|

PI-273, a Substrate-Competitive, Specific Small-Molecule Inhibitor of PI4KIIα, Inhibits the Growth of Breast Cancer Cells

Abstract: While phosphatidylinositol 4-kinase (PI4KIIa) has been identified as a potential target for antitumor therapy, the clinical applications of PI4KIIa are limited by a lack of specific inhibitors. Here we report the first small-molecule inhibitor (SMI) of human PI4KIIa. Docking-based and ligand-based virtual screening strategies were first employed to identify promising hits, followed by two rounds of kinase activity inhibition validation. 2-(3-(4-Chlorobenzoyl)thioureido)-4-ethyl-5-methylthiophene-3-carboxamide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Historically, the two PI4KII activities could not be distinguished in cell and tissue extracts and, unsurprisingly, the structure of the conserved core of PI4KIIβ is very similar to that of PI4KIIα . Recently an isoform‐selective small molecule inhibitor, PI‐273, has been developed that is approximately 30 times more potent against PI4KIIα than PI4KIIβ . This compound is capable of differentiating the two isoforms and is likely to become an important experimental tool.…”
Section: The Pi4kiis Are An Ancient Kinase Familymentioning
confidence: 99%
“…Historically, the two PI4KII activities could not be distinguished in cell and tissue extracts and, unsurprisingly, the structure of the conserved core of PI4KIIβ is very similar to that of PI4KIIα . Recently an isoform‐selective small molecule inhibitor, PI‐273, has been developed that is approximately 30 times more potent against PI4KIIα than PI4KIIβ . This compound is capable of differentiating the two isoforms and is likely to become an important experimental tool.…”
Section: The Pi4kiis Are An Ancient Kinase Familymentioning
confidence: 99%
“…S1). Importantly, there was no structural similarity between PI-273 (35) and any of the active compounds identified in this study.…”
Section: Development Of a Bret Assay To Monitor Pi4p Generation On Enmentioning
confidence: 63%
“…Based on all of these data linking type II PI4Ks to many physiological processes relevant to a variety of diseases, it would be desirable to find inhibitors for PI4K2A, the class of PI4Ks for which inhibitors are not available as yet. A recent study described an inhibitor (PI-273) of PI4K2A (35), which showed promise in inhibiting cancer cell growth. That study used docking-based and ligand-based screening strategy to identify PI-273, which was found to interfere with substrate binding or substrate access and not with ATP binding (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PI4K2A is targeted to the trans-Golgi network and lysosomes [29][30][31]. Recently, an increasing number of studies have identified PI4K2A as a potential target for breast cancer therapy [32][33][34]. These results improved our understanding of PI4K2A/PKR lysosome networks may lead to the development of unique and highly specific targeted therapies for cancer.…”
Section: Introductionmentioning
confidence: 97%